Direct EUV/X‐Ray Modulation of the Ionosphere During the August 2017 Total Solar Eclipse. Issue 9 (8th May 2018) - Mrak, Sebastijan; Semeter, Joshua; Drob, Douglas; Huba, J. D.
Abstract: The great American total solar eclipse of 21 August 2017 offered a fortuitous opportunity to study the response of the atmosphere and ionosphere using a myriad of ground instruments. We have used the network of U.S. Global Positioning System receivers to examine perturbations in maps of ionospheric total electron content (TEC). Coherent large‐scale variations in TEC have been interpreted by others as gravity wave‐induced traveling ionospheric disturbances. However, the solar disk had two active regions at that time, one near the center of the disk and one at the edge, which resulted in an irregular illumination pattern in the extreme ultraviolet (EUV)/X‐ray bands. Using detailed EUV occultation maps calculated from the National Aeronautics and Space Administration Solar Dynamics Observatory Atmospheric Imaging Assembly images, we show excellent agreement between TEC perturbations and computed gradients in EUV illumination. The results strongly suggest that prominent large‐scale TEC disturbances were consequences of direct EUV modulation, rather than gravity wave‐induced traveling ionospheric disturbances. Plain Language Summary: A total solar eclipse is a rare astronomical event, which offers an opportunity to study how the Sun interacts with our atmosphere in great detail. The solar irradiance at X‐ray and extreme ultra violet wavelengths is so energetic that it ionizes the neutral gases in the upper atmosphere, whereas longer wavelengths penetrate deeper in the atmosphere and heat it up. The great American total solar eclipse on 21 August 2017 offered an extraordinary opportunity to study the atmospheric response to the occulted solar disk at a time of its largest energy deposition (around noon time). The ionosphere is affected by variations in the solar illumination and by temperature changes in the lower atmosphere. We identified four large‐scale perturbations in ionospheric plasma using signals acquired from a large network of Global Positioning System receivers. For the first time, we show firm evidences that irregular solar flux deposition inside of the penumbra causes a continental‐wide modulation of the ionospheric plasma. Specifically, the observed disturbances were caused by two sunspots which created four stark deviations from a uniform solar disk model. The discovery of a direct solar modulation is a revolutionary turnabout, since the previous reports attributed the disturbances to thermospheric or stratospheric sources. Key Points: Two solar active regions caused prominent nonuniform regions inside of the penumbra at EUV/X‐ray wavelengths The irregular EUV illumination directly modulated ionospheric electron density, producing four distinct large‐scale TEC disturbances The 2‐D manifestation of the TEC disturbances matches the 2‐D projection of the EUV/X‐ray irregularities